Productivity Estimation of Copal based on Some Variables of Agatis Tree Phenotype (Agathis lorantifolia, Salisb) in Mount Walat Educational Forest - Edje Djamhuri; Muhaemin . (Jurnal Silvikultur Tropika, 2014)
Selection process to obtain agatis tree of leaky copal need a long time. So, neeeded a fast way to estimate copal leaky tree based on variable of tree phenotype. This research aims to produce estimation model of copal productivity and explain the tightness of relationship level among copal productivity with some variable of tree phenotype and between variables of phenotype tree. Analysis uses double linier regresion with four phenotype variables, such as stem diameter, bark thickness, total height, and canopy volume. Based on analysis result, the best model is ŷ = –1.445 + 6.072x1 + 0.016x2 + e with R2 = 49.3%, x1 = bark thickness and x2 = canopy volume. Copal productivity has strong positive correlation significant with canopy volume (r = 0.601), moderate positive correlated with diameter (r = 0.550) and bark thickness (r = 0.469) and aslo low positive correlated sygnificant with total height (r = 0.355). Stem diameter has moderate positive correlation with bark thickness (r = 0.594), total height (r = 0.478), and canopy volume (r = 0.470). Bark thickness is positively low correlated not significant with total height (r = 0.209) and canopy volume (r = 0.189). Tree height is strong positive correlated with canopy volume (r = 0.628).